What is the meaning of urban liveability for a city in a low-to-middle-income country? Contextualising liveability for Bangkok, Thailand - Amanda Alderton; Melanie Davern; Kornsupha Nitvimol; Iain Butterworth; Carl Higgs; Elizabeth Ryan; Hannah Badland (BMC, 2019)
Abstract Background Creating 'liveable' cities has become a priority for various sectors, including those tasked with improving population health and reducing inequities. Two-thirds of the world's population will live in cities by 2050, with the most rapid urbanisation in low- and middle-income countries (LMIC). However, there is limited guidance about what constitutes a liveable city from a LMIC perspective, with most of the evidence relating to high-income countries, such as Australia. Existing liveability frameworks include features such as public transport, affordable housing, and public open space; however, these frameworks may not capture all of the liveability considerations for cities in LMIC contexts. Objectives This case study formed a multi-sectoral partnership between academics, policymakers (Bangkok Metropolitan Administration, Victorian (Australia) Department of Health and Human Services), and a non-government organisation (UN Global Compact - Cities Programme). This study aimed to: 1) conceptualise and prioritise components of urban liveability within the Bangkok, Thailand context; 2) identify alignment to or divergence from other existing liveability tools; and 3) identify potential indicators and data sources for use within a Pilot Bangkok Liveability Framework. Methods The Urban Liveability Workshop involving technical leaders from the Bangkok Metropolitan Administration and a rapid review of liveability literature informed the conceptualisation of liveability for Bangkok. The Bangkok Metropolitan Administration Working Group and key informants in Bangkok provided input into the liveability framework. Indicators identified for Bangkok were mapped onto existing liveability tools, including the UN Global Compact CityScan. Results Findings revealed commonalities with the Australian liveability definition, as well as new potential indicators for Bangkok. The resulting Pilot Bangkok Liveability Framework provides a structure for measuring liveability in Bangkok that can be implemented by the Bangkok Metropolitan Administration immediately, pending appropriate data acquisition and licensing. The Bangkok Metropolitan Administration Working Group and key informants identified core issues for implementation, including limited spatial data available at the district-level or lower. Conclusions This study conceptualised urban liveability for Bangkok, a city in a LMIC context, with potential for adjustment to other cities. Future work should leverage opportunities for using open source data, building local capacity in spatial data expertise, and knowledge sharing between cities.